Feeding hydroalcoholic extract powder of Lepidium meyenii (maca) enhances testicular gene expression of 3β‐hydroxysteroid dehydrogenase in rats. (6th March 2017) - Ohta, Y.; Kawate, N.; Inaba, T.; Morii, H.; Takahashi, K.; Tamada, H.
Summary: Although feeding diets containing the extract powder of Lepidium meyenii (maca), a plant growing in Peru's Central Andes, increases serum testosterone concentration associated with enhanced ability of testosterone production by Leydig cells in male rats, changes in testicular steroidogenesis‐related factors by the maca treatment are not known. This study examined the effects of maca on testicular gene expressions for luteinizing hormone receptor, steroidogenic acute regulatory protein and steroidogenic enzymes. Eight‐week‐old male rats were given the diets with or without (control) the maca extract powder (2%) for 6 weeks, and mRNA levels were determined by reverse transcription quantitative real‐time PCR. The results showed that the testicular mRNA level of HSD3B1 (3β‐hydroxysteroid dehydrogenase; 3β‐HSD) increased by the treatment, whereas the levels of the other factors examined did not change. These results suggest that increased expression of 3β‐HSD gene may be involved in the enhanced steroidogenic ability by the maca treatment in rat testes.